Zinc removal by natural microflora - Izwan, Abdul Rahman (2009)
Different kinds of heavy metals exist in the solution with different forms, so their treatment methods are also different. As for the treatment of heavy metal wastewater, many methods have been put forward at home and abroad, including chemical-treatment method, ion-exchange method, electrolytic method, adsorption method, reverse-osmosis method, evaporating concentration and biological treatment. This study used biological treatment to degrade zinc from wastewater. Zinc removal by natural microflora was studied by using sequencing batch reactor(SBR). 5 reactors were used in this studies; 1 10L reactor for accclimatization and 4 5L reactors for treatment. 1 month was used to acclimatize the microflora. Treatment reactors were run for 2 weeks. Every treatment reactor was set to run at specific loading rate which were ranging from 5 mg/L.d to 3 mg/L.d. This study was run to study the effects of different loading rate on the zinc waste treatment, to study the effects of zinc concentration to the growth of microflora and to study the degradation of zinc by microflora in soil.During the run, about 48-88% of zinc and about 30-48% of COD were removed. Mathematical calculation by Design Expert predicted that LR5 gives the maximum value of removal with 39.83% COD removal and 80.81% zinc removal at 486.74 mg/L suspended solid. This study shows that higher LR rate gives higher value of zinc and COD removal but gives lower value of SS.-Author-